Effect of carbon dioxide (CO2) and oxygen (O2) levels on quality of ‘Palmer’ mangoes under controlled atmosphere storage - de Almeida Teixeira, Gustavo Henrique [UNESP]; Santos, Leandra Oliveira; Cunha Júnior, Luis Carlos; Durigan, José Fernando [UNESP] (Springer Nature, 2018)
With the objective to evaluate the modifications in the fruit quality, ‘Palmer’ mangoes were stored at 12.8 °C for 30 days in controlled atmosphere storage that contained a low level of oxygen (5 kPa) which was associated with increasing levels of carbon dioxide CO2 (0, 1, 5, 10, 15 and 20 kPa CO2). Controlled atmosphere storage did not effect mango respiration. However, transfer mangoes, that were previously stored at high levels of CO2 (5 kPa O2 + 15 kPa CO2 and 5 kPa O2 + 20 kPa CO2) to ambient temperature presented higher respiratory rates. No significant effects of increasing CO2 levels on color (L*, chromaticity, and hue angle), firmness, physical–chemical parameter and carbohydrate metabolism (total and reducing sugars, soluble pectin) were observed. After transfer to ambient temperature the mangoes ripened normally without any signs of CO2 injury. Therefore, the increment levels of CO2 neither improved the quality of the ‘Palmer’ mangoes nor presented a synergistic effect with low-oxygen when compared to 5 kPa O2-control.
Keywords: Carbohydrates; Mangifera indica L; Pectin; Respiration; Shelf-life; Softening